Life signals detection system based on a continuous‐wave X‐band radar. Issue 23 (1st November 2016) - Donelli, M.; Viani, F.
Abstract : An experimental bistatic X‐band continuous‐wave life‐detection radar is proposed. The system operates with two directive high gain antennas and a programmable transmitter and receiver. A method based on the independent component analysis, and accurate breath and heartbeat movements models are applied to suppress the interference and to better identify the respiratory and heart movements. The obtained experimental results show that this system can effectively detect the heartbeat and the respiratory activity with a good accuracy and demonstrated the capabilities and the potentialities of such system.